A gap identification in Muslim-friendly hotel research in Malaysia: a systematic literature review approach - Rahim, Noraini; Wan Ismail, Wan Rusni; Abdul Rahman, Nuradibah; Abu Bakar, Ahmad Redhuan (Universiti Teknologi MARA (UiTM), Malaysia, 2025)
The Muslim-Friendly Hotel (MFH) is a concept introduced by the hotel industry to cater for a market segment that seeks accommodations that meet specific characteristics. Despite the increase of MFH establishments worldwide, research in this area is still in its infancy, and this study aims to investigate the immature areas related to MFH research. This study is conducted using the systematic review, following the Reporting Standards for Systematic Evidence Syntheses (ROSES) guidelines. Overall, the themes indicate gaps in current literature as these themes evolved around issues related to hotel facilities, regulations, standardisation, sustainable practice involving environmental issues and guest acceptance.